COVID-19 pandemic and labor commitment: relationship within an organization of the colombian electricity sector (2022)
The objective of this research is to analyze the relationship and impact of the Covid19 pandemic on the commitment of employees of an organization in the Colombian electricity sector, through a non-experimental, cross-sectional, correlational / causal design and with a quantitative approach. The sample corresponded to 113 workers linked to the analyzed organization and the information was collected through a web-type survey. The results establish a significant relationship between changes in working and daily conditions due to the Covid19 Pandemic as an independent variable, and work commitment as a dependent variable, of r = 0.565. Likewise, the self-perception of work commitment and adaptation to the new work context in the people surveyed amounts to more than 92% in a strong or very strong way. In this sense, the studied company should consider strategies to limit the working day, since 61.06% of those surveyed consider that their working time has increased since they are performing it remotely.